GENETIC POTENTIAL OF EDILBAYSKY BREED SHEEP OF ESPC «AGRO BAYSERKE» HEARD - Dosmukhambetov T.M.; Sadykulov T.; Kineyev M.A.; Ivanov N.P.; Aliyev M.А. (Scientific Journal of Pedagogy and Economics, 2019)
Results the article are shown in of studying of breeding herd of sheep of edilbaysky breed the created in new climatic conditions of «Bayserke Agro» ESPC of Almaty region to them are given in article. The main economic and useful sign of this breed – precocity of lambs for the lactic period of development.